Pagrindiniu dailiojo ciuožimo elementu mokymas naudojant pagalbinius pratimus - Paramonova, N.; Meliochin, A.; Tokarevskaja, I. (Sporto Mokslas-Sport Science, 2015)
Figure skating is a type of sports that requires high level coordination of movements. In order to study the basics of figure skating successfully, one must use a combined method involving both separation and integration. Such method presumes utilization of lead-up exercises. Lead-up exercises are employed to make mastering of athletic technique easier by systematic learning of basic movements that ensures performing of main movements. This possibility is due to the related origin of both lead-up and main movements. Learning efficiency of the methods employed to master athletic technique, it largely depends on the quantity, complexity, and peculiarities of the utilized exercises. While learning movements that require complex coordination, it is essential to select a variety of exercises that are joined by the same training program, starting position, preparatory, and main movements and differ only in complexity of coordination. During the early period of teaching, lead-up exercises can be used to help athletes understand kinematic, dynamic, and rhythmic characteristics of the main areas of support. This study aims to consider the use of lead-up exercises in order to master basic elements of gliding in figure skating during the elementary teaching.